PREFER ENSI PELAKU PASAR DALAM MEMILIH INSTRUMEN PASAR UANG ANTAR BANK SYARIAH: PENDEKATAN ANALYTICAL HIERARCHY PROCESS (AHP) - Dida Nurhaida (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2018)
This research aims to describe, compare and analyze the Sharia Banks’ preferences for selecting Islamic interbank money market instrument in Indonesia to manage their liquidity, what is the reason and research what factors determines market choices in the future. Data collection through in-depth interviews through questionnaires to market participants consisting of 7 Islamic banks representing 97% of all Islamic Banking Institutions in Jakarta. The survey was conducted in October 2017. The empirical analysis tool used in this study is the AHP model based on several criteria for the preferences of market players. The liquidity instruments in the Sharia Interbank Money Market in Indonesia are still lack in variance. Among the 3 (three) instruments available: 1) Interbank Mudharaba Investment Certificate (SiMA), 2) Interbank Sharia Commodity Trading Certificate (SiKA), and 3) Sharia Repo, only SiMA is often transacted. Arguing that: 1) SiMA is most widely known and available in the market; 2) The mechanism of SiMA is not complicated, it‟s simple profit-sharing calculation and bookkeeping also easier; 3) SiMA is relatively easy to run especially for its settlement compared to Sharia Repo and SiKA which require underlying settlement.